PENGARUH UMUR DAN INTERVAL PERSALINAN TERHADAP KEJADIAN PREEKLAMSI DI KABUPATEN BANYUMAS - Fajarsari, Dyah; Prabandari, Fitria (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Preeclampsia is one of the causes of the high maternal mortality rate in Indonesia. Risk factors for preeclampsia are age, parity, history of preeclampsia, family history of preeclampsia, history of illness, labor interval and BMI. The causes of maternal death were pre-eclampsia-eclampsia (28.76%), bleeding (22.42%), infection (3.54%). In Banyumas Regency eclamation and bleeding are quite large contributors, namely 14 and 5 cases respectively. The aim of the study: to analyze the effect of age and labor interval on the incidence of preeclampsia in Banyumas Regency. The type of research is analytical survey with retrospective case control approach. The population in this study were pregnant women with pre-eclampsia in five health centers with the highest number of pre-eclampsia in Banyumas in the last 3 months. Samples in this study used a total sampling technique, namely 60 pregnant women diagnosed with pre-eclampsia as a case group and as many as 60 respondents. normal pregnancy. The results of the study of risk factors that influence the incidence of pre-eclampsia are age (Ï: 0.009), labor interval (Ï: 0.009). Conclusion: Age of pregnant women aged> 35 years has a risk of developing preeclampsia of 2,970 times compared to pregnant women aged <35 years, while labor intervals> 5 years have a risk of preeclampsia of 0.242 times compared to pregnant women who have labor intervals <5 year. Â  Keywords: Preeclampsia, Age, Labor Interval.